(untitled) (Journal of Small Business Strategy (archive only), 2010)
This paper presents the results of a ten year longitudinal analysis of almost 19,000 Polish manufacturing firms engaged in export operations. Export dynamics was measured by the rate of growth, consistency of export sales and survival in international operations. It was found that early involvement in international activities negatively affected the survival and regularity of sales of small exporters but that had a positive impact on larger exporters. A strong commitment to internationalization and a capacity for managing rapid growth are factors in achieving high growth in international sales over time. Managerial implications include recognizing the risk of possible failure when they enter international markets, and take into account that export volumes may stagnate after a first opportunity and not justify the initial effort to expand abroad. To remedy such unfavorable outcomes, managers should plan carefully before entering export markets or undertaking subsequent phases of export growth.